Religião da arte e tragédia grega na "fenomenologia do Espírito" de G. W. F. Hegel - Garcia, Marcio Lourenço (2013)
The Greek tragedy, in the Hegelian scheme, is situated as an eloquent sign of the final moment of the religion of art, then, is this step that takes place a painful schism between the state law and the family law. Then, in the tragedy, the need of the concept, still unconscious-of-itself, approaches the content of the life of the tragic hero s fate, as well as the language of minstrel ceases to be impersonal (as in epic) and actively participates in this content as actor. He actively participates in the drama and can interfere in the drama, its language indicates the pain of the hero. The ancient tragedy begins, then, to realize the unity of the gods as claimed by the philosophers of antiquity, and will culminate in a comedy in which happens the process of the absolutism of the Self and the passage of the happy consciousness for the unhappy consciousness. The progressive manifestation of the Spirit can be translated by the movement of get out of immediate substance, viewed in the religion of art, which supersedes the moments of the abstract work of art and of the living work of art, resulting in the spiritual work of art. This movement means the output of the substance for himself, because it claims the recognition of their uniqueness by the collective. Moreover, the Self is the creator of the singularity in the religion of art and, in the development of tragedy, is tool for self-knowledge of the Spirit in its moments, in the time, because his self-consciousness reveals itself through the universal powers offended and to seek revenge, because such a religion of art is like the mirror of the Spirit. This content is actually present, therefore, in itself, is a thing, and to the consciousness another. The right upper and the lower receive the significance that the first represents the power that knows, which manifests itself to consciousness, and, the second takes the meaning of power that escapes the consciousness and hides in the underworld of the Erinyes. This same religion of art sharpens the mind and imagination of all spectators to get up a flight to the heights of the consideration of his life in the city, the human and divine right - the first one as the female character, and, the second, the male - in the flow of logical necessity and that is the fate of total Spirit: the tragedy shows that there is no existence that is not already divided in itself and that this opposition is to the highest good of all the unity of the Spirit.